Role of microglia adenosine A(2A) receptors in retinal and brain neurodegenerative diseases - Santiago, Ana R. (2014)
Neuroinflammation mediated by microglial cells in the brain has been commonly associated with neurodegenerative diseases. Whether this microglia-mediated neuroinflammation is cause or consequence of neurodegeneration is still a matter of controversy. However, it is unequivocal that chronic neuroinflammation plays a role in disease progression and halting that process represents a potential therapeutic strategy. The neuromodulator adenosine emerges as a promising targeting candidate based on its ability to regulate microglial proliferation, chemotaxis, and reactivity through the activation of its G protein coupled A2A receptor (A2AR). This is in striking agreement with the ability of A2AR blockade to control several brain diseases. Retinal degenerative diseases have been also associated with microglia-mediated neuroinflammation, but the role of A2AR has been scarcely explored. This review aims to compare inflammatory features of Parkinson's and Alzheimer's diseases with glaucoma and diabetic retinopathy, discussing the therapeutic potential of A2AR in these degenerative conditions.